Economic diplomacy of Denmark under the first government of Mette Frederiksen (2019-2022) - Sušienka, Martin (2023)
The aim of the thesis was to study economic diplomacy of Denmark under the first government of Mette Frederiksen, in the period between June 2019 and December 2022. The thesis focused on evaluation of general goals and government-specific goals identified in strategic documents relevant to the given period. By means of quantitative analysis and content analysis, the thesis aimed at answering the research question “To what extent has the first government of Danish Prime Minister Mette Frederiksen followed its goals and strategy in the area of economic diplomacy?” The analysis showed that the conduct of economic diplomacy of Denmark was rather successful, achieving the success rate of more than 80%, based on the chosen approach. Interviews with four high-ranking officials and managers were introduced at the end for the purpose of triangulation.